Editorial: The biology and conservation of elasmobranchs and chimaeras - Bengil, Elizabeth Grace Tunka; Basusta, Nuri (Frontiers Media Sa, 2024)
[Abstract Not Available]
Keywords: conservation; management; contemporary approaches; elasmobranchs; chimaeras